Hubungan Pola Asuh Orang Tua Dengan Hasil Belajar Pkn Siswa SD Negeri 2 Caracas - Merdekawati Hisby; E. Kosasih (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Parenting style is a way that parents use in trying various strategies to encourage children to achieve the desired goals. Parenting style is a reflection of parental behavior that is applied to children. It affects the learning achievement in schools, especially for elementary school children. This study aimed to determine (1) the relationship between parenting style with Civics learning outcomes, and (2) the parenting style applied by parents in democratic, authoritarian and permissive types. This research was conducted at State Primary School 2 of Caracas in 2018/2019 academic year. This research used a quantitative approach with the correlation method analysis. The subjects were 38 students in fifth grade. The data collection techniques were in the form of observation and questionnaires. The hypothesis test of this research was the product moment correlation coefficient analysis. The results of this study indicate that there is a positive relationship between parenting style with Civic learning outcomes of fifth grade students of State Primary School 2 of Caracas with a correlation of 12.1%. The correlation between parenting style and democratic type was 17%, authoritarian type was 13.1% and permissive type was 12.2%. This study proposed parents to adjust and observed their parenting style by looking at their children learning outcomes.